Effects of weight loss rate on myostatin and follistatin dynamics in patients with obesity - Kurose, Satoshi; Onishi, Katsuko; Miyauchi, Takumi; Takahashi, Kazuhisa; Kimura, Yutaka (Frontiers in Endocrinology, 2024)
Background: Exercise-induced cytokines involved in controlling body composition include myostatin (MST) and follistatin (FST), both of which are influenced by physical activity. This study investigated changes in body composition and physical activity during a weight loss program, as well as the impact on serum MST and FST levels at various weight loss rates.Methods: A total of 126 patients with obesity who completed a 6-month weight loss program were divided into three groups based on weight loss rate (%): low (< 3%), middle (3-10%), and high (≥10%). The International Physical Activity Questionnaire was used for assessing physical activity, whereas dual X-ray absorptiometry was used to determine body composition. Serum MST and FST levels were measured using the enzyme-linked immunosorbent assay.The middle and high groups showed a significant decrease in percent body fat and a significant increase in percent lean body mass and physical activity. Serum MST levels increased significantly in all three groups, although FST levels reduced significantly only in the middle group. After adjusting for sex and body composition, changes in peak oxygen intake (β = -0.359) and serum FST levels (β = -0.461) were identified as independent factors for the change in MST levels in the low group. Sex (β = -0.420) and changes in MST levels (β = -0.525) were identified as independent factors for the change in serum FST levels in the low group, whereas in the high group, sitting time (β = -0.600) during the weight loss program was identified as an independent factor for change in serum FST levels.Serum MST levels in patients with obesity increased significantly following the weight loss program, independent of weight loss rate. In contrast, serum FST levels reduced significantly only in the 3-10% weight loss group. These findings indicate that MST and FST secretion dynamics may fluctuate in response to physical activity, while also reflecting feedback regulation of body composition and metabolism during weight reduction.